Intention-based sharing - Daniela Di Cagno; Arianna Galliera; Werner Güth; Luca Panaccione (Games, 2018)
How are allocation results affected by information that another anonymous participant intends to be more or less generous? We explore this experimentally via two participants facing the same allocation task with only one actually giving after possible adjustment of own generosity based on the other's intended generosity. Participants successively face three game types, the ultimatum, yes-no and impunity game, or (between subjects) in the reverse order. Although only the impunity game appeals to intrinsic generosity, we confirm conditioning even when sanctioning is possible. Based on our data, we distinguish two major types of participants in all three games: one yielding to the weakest social influence and the other immune to it and offering much less. This is particularly interesting in the impunity game where other-regarding concerns are minimal.
Keywords: 330; (conditional) generosity; ultimatum game; yes-no game; impunity game; experiments